The Unique Properties of Moringa Oleifera Extract in Soap Optimization: A Scientific Approach - Diah Miftahul Aini; Baiq Desy Ratnasari (Indonesian Journal of Global Health Research, 2024)
Moringa leaves (Moringa oleifera), a valuable source of bioactive compounds, including flavonoids, phenolic acids, tannin, and terpenoids. These compounds provide significant benefits to the skin, due to their antioxidant, anti-inflammatory, and antimicrobial properties. The chemical composition of these leaves has been demonstrated to enhance dermal hydration and provide protection against environmental stressors. By balancing Moringa with other natural ingredients such as coconut, olive, and palm oil, the efficacy of skincare formulation can be optimized, resulting in improved texture, stability, and consumer appeal. This research aims to optimize the soap's effectiveness by enhancing its properties, such as cleansing, moisturizing, and antimicrobial functions, using the unique characteristics of Moringa oleifera. The initial step involved of an ethanol extract of Moringa leaves, which was then subjected to analysis using Gas Chromatography-Mass Spectrometry (GC-MS). The analysis revealed that Moringa leaves contain eight key compounds, including 2.4(1H,3H)-pyrimidineodione, glycerol, 2,3-dihydro-3,5-dihydroxy-6-methyl-, 4,3-allyl-6-methoxyphenol, epoxylinalool, 1H-pyrrole, 2-(2,4,6-heptatrienyl), tetradecanoics acid, and hexadecanoic acid. The aforementioned compounds were used to formulate a soap base containing Moringa leaves. The resulting soap exhibit a pleasant fragrance, a dense texture, yellow slightly white in color, and a pH of 10, as confirmed by organoleptic and pH test. The recent focus resulting in the development of Moringa-based skincare product that are not only effective but also eco-friendly. Present study represents a promising approach to natural solution that cater to diverse skin types and consumer preferences.